Navigating the promise and perils of village autonomy: Insights from Kepulauan Meranti, Indonesia - Robert Saputra; Tomáš Havlíček (Dynamics of Rural Society Journal)
This study investigates the impact of village autonomy on rural development in Indonesia which focuses on the implementation of Village Law No. 6/2014. The objective of this research includes: (1) analyzing the implementation of decentralization in rural Indonesia through Village Law No. 6/2014, (2) assessing the effects of village autonomy on rural development, and (3) identifying factors mediating the relationship between village autonomy and rural development. This research further uses a mixed-methods approach, including quantitative analysis and field observations. This study evaluates key variables such as resource allocation, access to services, participation, social cohesion, and economic opportunities. Results of the study indicates that village autonomy, particularly access to services and economic opportunities, significantly influences rural development. Village Law No. 6/2014 has empowered local government through increased decision-making authority, financial allocation, and community participation. However, challenges such as reliance on intergovernmental transfers, limited administrative capacity, and government inefficiencies hinder its full potential. This study identifies institutional environments and local governance practices as critical mediators, emphasizing the need for transparency, participatory planning, and capacity building. Additionally, the cash-for-work program (Padat Karya Tunai - PKT) is highlighted as a complementary strategy to enhance rural livelihoods and infrastructure. This research concludes that integrating PKT with village autonomy policies can foster inclusive and sustainable rural development. Recommendations include expanding PKT, improving governance mechanisms, and ensuring equitable resource distribution to address underdevelopment in rural Indonesia. These findings provide valuable insights for policymakers and practitioners seeking to design more effective governance frameworks and targeted interventions which support equitable growth and resilience in rural communities.